Rationale and significance of patient selection in awake prone positioning for COVID-19 pneumonia. Issue 3 (10th September 2020) - Huang, Ching-Feng; Tay, Chee Kiang; Zhuang, Ya-Fang; Liu, Jiaxuan; Sewa, Duu Wen
We read with interest the research letter by Ng et al. [1], which described their experience in prone positioning (PP) for awake patients with coronavirus disease 2019 (COVID-19) pneumonia, and concluded that this manoeuvre could delay or reduce the need for intensive care. We agree that the authors demonstrated safety and feasibility of PP in COVID-19 pneumonia patients. However, we humbly suggest a few crucial points be addressed before drawing conclusions on the efficacy of PP. COVID-19 is increasingly recognised to manifest phenotypic diversity in clinical presentation, severity and trajectory. As such, treatment, e.g. awake prone positioning, should be personalised and guided by the primary pathophysiology and immunopathology. https://bit.ly/2ZneHlF